2019
DOI: 10.48550/arxiv.1903.00655
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Bayesian Nonparametric Estimation to Entropy

Abstract: A Bayesian nonparametric estimator to entropy is proposed. The derivation of the new estimator relies on using the Dirichlet process and adapting the well-known frequentist estimators of Vasicek (1976) and Ebrahimi, Pflughoeft and Soofi (1994). Several theoretical properties, such as consistency, of the proposed estimator are obtained. The quality of the proposed estimator has been investigated through several examples, in which it exhibits excellent performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This difficulty can be avoided by setting an appropriate value of a as otherwise the prior G will become too influential. Al-Labadi et al (2019d) suggested to choose a to be at most n/2. For estimation purposes, from (5),…”
Section: Mutual Information Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…This difficulty can be avoided by setting an appropriate value of a as otherwise the prior G will become too influential. Al-Labadi et al (2019d) suggested to choose a to be at most n/2. For estimation purposes, from (5),…”
Section: Mutual Information Estimationmentioning
confidence: 99%
“…See for example, Vasicek (1976), Ebrahimi et al (1994), Alizadeh Noughabi (2010), Alizadeh Noughabi and Alizadeh Noughabi (2013) and Al-Omari (2014. Also, Al-Labadi et al (2019d) proposed an efficient Bayesian counterpart of Vasicek's estimator. For the multivariate (joint) entropy estimation, some frequentist procedures have been offered in the literature; see, for instance, Kozachenko and Leonenko (1987), Misra et al (2010), Sricharan and Hero (2012), Sricharan et al (2013), Gao et al (2016), Berrett et al (2019a), Ba and Lo (2019) and the references therein.…”
Section: Introductionmentioning
confidence: 99%